Effect of Chronic Disease Management Program (Prolanis) on Blood Sugar Levels in Patients with Diabetes Mellitus - Silvia, Eliza; Safrizal; Siregar, Siti Maisyaroh; Anwar, Sufyan (Jurnal EduHealth, 2023)
Diabetes Mellitus (DM) is a chronic disease that has a serious impact on public health throughout the world. The Chronic Disease Management Program (Prolanis) is a program designed to provide a comprehensive approach to the management of chronic diseases, including Diabetes Mellitus. The purpose of this study was to evaluate the effect of the Prolanis program on controlling blood sugar levels in people with Diabetes Mellitus. This study used an experimental method with a pre-test and post-test research design, in which the intervention group received the Prolanis program for a certain period, while the control group did not receive additional intervention. Data was collected by examining blood sugar levels before and after the intervention period. The research sample consisted of type 2 Diabetes Mellitus sufferers who had been enrolled in the Prolanis program. The results of this study indicate that the Prolanis program has a positive effect on controlling blood sugar levels in people with Diabetes Mellitus. The intervention group experienced a significant decrease in average blood sugar levels after participating in the Prolanis program. On the other hand, the control group that did not receive the intervention showed insignificant changes in blood sugar levels. These findings support the effectiveness of the Prolanis program in helping control blood sugar levels in people with Diabetes Mellitus. A comprehensive approach that includes education about diet, physical activity.